EFEK ANTIDIARE EKSTRAK ETANOL UMBI RUMPUT TEKI (Cyperus rotundus L.) TERHADAP MENCIT PUTIH - Rifda Naufa Lina; Monik Dewi Astutik (Universitas Wahid Hasyim Semarang, 2020)
ABSTRACT Diarrhea is a disease characterized by stimulation of bowel movements continuously and feces that are not formed or liquid that has a frequency of more than 3 times in 24 hours. The incidence of diarrhea can occur throughout the world and causes 4% of all deaths and 5% of health losses to cause disability. Cyperus rotundus L. can be used as an antidiarrheal drug because it contains a compound such as tannins and flavonoids. This research is an experimental study with a Post-test only Control Group Design. The subjects using white male mice (Mus muscullus) 25 mice and divided into 5 groups: positive control, negative control, ethanol extracts of rubers Cyperus rotundus L. with a dose of 250 mg/kgBB, 500 mg/kgBB and 1000 mg/kgBB. Before the treatment, mice fasted and induced diarrhea (oleum ricini). Obsevations was made by observing the parameters of diarrhea: duration of diarrhea, frequency of diarrhea and feces consistency every 30 minutes for 4 hours. The numerical data was then processed using SPSS with one way ANOVA test. The results obtained showed that the administration of extract with a dose of 250 mg/kgBB, 500 mg/kgBB and 1000 mg/kgBB had an antidarrheal with effective dose is 500 mg/kgBB. Keywords: antidiarrheal, ethanol extract of tubers Cyperus rotundus L., oleum ricini, Cyperus rotundus